2023
DOI: 10.1097/inf.0000000000004054
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Real-time TDM-guided Pharmacodynamic Target Attainment of Continuous Infusion Beta-lactam Monotherapy and Microbiologic Outcome in the Treatment of Critically Ill Children With Severe Documented Gram-negative Infections

Milo Gatti,
Caterina Campoli,
Maria Elena Latrofa
et al.

Abstract: Objectives: To explore the relationship between real-time therapeutic drug monitoring (TDM)-guided pharmacodynamic target attainment of continuous infusion (CI) beta-lactam monotherapy and microbiological outcome in the treatment of critically ill children with severe documented Gram-negative infections. Methods: Observational, monocentric, retrospective study of critically ill patients receiving CI piperacillin-tazobactam, ceftazidime, or meropenem in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Also, MIC values against Gram-negative bacterial isolates, being above the EUCAST clinical breakpoint, emerged as an independent predictor of failure in attaining early optimal PK/PD targets among OLT recipients treated with beta-lactams. A recent study conducted among 21 critically ill pediatric patients showed that quasi-optimal/suboptimal beta-lactam PK/PD target attainment occurred more frequently among patients having infections caused by less susceptible pathogens with borderline in vitro susceptibility [42]. Clearly, this is in agreement with the fact that the beta-lactam doses for properly dealing with this issue should be higher than the standard ones [43].…”
Section: Discussionmentioning
confidence: 70%
“…Also, MIC values against Gram-negative bacterial isolates, being above the EUCAST clinical breakpoint, emerged as an independent predictor of failure in attaining early optimal PK/PD targets among OLT recipients treated with beta-lactams. A recent study conducted among 21 critically ill pediatric patients showed that quasi-optimal/suboptimal beta-lactam PK/PD target attainment occurred more frequently among patients having infections caused by less susceptible pathogens with borderline in vitro susceptibility [42]. Clearly, this is in agreement with the fact that the beta-lactam doses for properly dealing with this issue should be higher than the standard ones [43].…”
Section: Discussionmentioning
confidence: 70%